COVID-19 Pulmonary Pathology, Ventilator-Induced Lung Injury (VILI), or Sepsis-Induced Acute Respiratory Distress Syndrome (ARDS)? Healthcare Considerations Arising From an Autopsy Case and Miny-Review - Roberto Scendoni; Diego Gattari; Mariano Cingolani (SAGE Publishing, 2022)
Acute respiratory distress syndrome (ARDS) caused by coronavirus disease (COVID-19) is a serious complication that requires early recognition. Autopsy reports or biopsies of the lungs in patients with COVID-19 revealed diffuse alveolar damage (DAD) at different stages; the fibrotic phase is usually associated with long-standing severe disease. Care management of hospitalized patients is not easy, given that the risk of incurring a ventilator-induced lung injury (VILI) is high. Additionally, if the patient develops nosocomial infections, sepsis-induced ARDS should be considered in the study of the pathophysiological processes. We present an autopsy case of a hospitalized patient whose death was linked to COVID-19 infection, with the histopathological pattern of advanced pulmonary fibrosis. After prolonged use of non-invasive and invasive ventilation, the patient developed polymicrobial superinfection oh the lungs. After analyzing the individual's clinical history and pulmonary anatomopathological findings, we consider healthcare issues that should lead to an improvement in diagnosis and to more adequate standards of care management among health professionals.